Vaccine waning and mumps re-emergence in the USA. (4th October 2017) - Lewnard, Joseph; Grad, Yonatan H
Abstract: Background: Following decades of declining mumps incidence amid widespread vaccination, the US has experienced a resurgence in mumps cases since 2006 driven largely by outbreaks on college campuses. The occurrence of cases among previously-vaccinated individuals and in communities with high vaccine coverage has prompted concerns about performance of the live attenuated mumps vaccine (Jeryl Lynn strain) currently included in the measles-mumps-rubella (MMR) series. It is unclear whether the resurgence is due to antigenic changes in circulating mumps virus, which would warrant consideration of a new vaccine, or to waning vaccine-derived protection, necessitating additional booster doses. Methods: We pooled data from studies of vaccine effectiveness to test for waning of protection. We used mathematical models to measure changes in population immunity since mumps vaccine introduction and to assess whether recent mumps transmission dynamics are consistent with hypotheses of waning immunity or vaccine escape. Results: We estimate that vaccine-derived protection persists, on average, 29 (95% CI: 17–54) years after receipt of the last dose (Fig. 1). This waning accounts for 66.4% of unexplained variation in estimates of mumps vaccine effectiveness across published studies. Changes in age-specific susceptibility due to vaccine waning and declining transmission track with the current resurgence in cases among young adults in the USA, and explain outbreaks reported among vaccinated adolescents during the late 1980s (Fig. 2). In contrast, vaccine escape would not be expected to result in cases following the observed age distribution (Fig. 3). Routine adult booster vaccination is needed to sustain mumps elimination. Conclusion: The resurgence of mumps in the USA since 2006 is attributable to waning of vaccine-derived immunity, suggesting the need for booster doses in adulthood. Trials are needed to assess clinical protection afforded by booster doses in individuals with a history of MMR vaccination. Disclosures: J. Lewnard, Pfier: Grant Investigator, Research grant